PD-L1 is upregulated in CD163+ tonsillar macrophages from children undergoing EBV primary infection - Moyano, Agustina; Ferressini, Natalia; De Matteo, Elena; Preciado, Maria Victoria; Chabay, Paola (Frontiers in Immunology, 2022)
Epstein Barr Virus (EBV) is a tumor associated virus that modulates, not only the infected cells but also innate and adaptive immunity. Macrophages play a key role in tumor development and progression. Particularly, M2 phenotype (CD163) with anti-inflammatory activity contributes to a favorable microenvironment for tumor development while M1(CD68) proinflammatory phenotype contributes to a restrictive one. In the context of pediatric EBV infection, little is known about macrophage contribution to PD-L1 expression, a molecule involved in immune exhaustion. We studied tonsils of primary infected (PI), healthy carriers (HC), reactivated (R) and not infected (NI) pediatric patients. Positive correlations were demonstrated for CD68+PD-L1+ in R and for CD163+PD-L1+ only in PI. Furthermore, CD163+PD-L1+ cell numbers were higher than PD-L1+CD68+ in PI patients. In addition, a positive correlation between PD-L1+CD163+ cells and LMP1 viral latent protein was observed in PI patients, and a positive correlation between PD-L1+CD68+ cells and BMRF1 lytic antigen was demonstrated. A positive correlation between TGF-β and PD-L1 expression was demonstrated in HC patients. Our findings indicate that EBV´s lytic and latent antigens might be regulating macrophages´ PD-L1 expression, in particular in PI patients, whereas, surprisingly, only TGF-β could be related to total PD-L1 upregulation. Given the relevance of macrophages and PD-1/PD-L1 pathway in tumor progression and survival, more studies in early EBV infection could help to develop EBV associated tumor therapies